Measuring customer satisfaction based on operational time on Al-Arafah Islami Bank Limited; Mirpur 10 branch - Sakif, Tanvir Ahmed (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.